Ever the hunted - Summerill, Erin, 1978- (Summerill, Erin, 1978- Clash of kingdoms novel., 2016)
Seventeen year-old Britta Flannery is the outcast daughter of a bounty hunter who must use her powers to track her father's killer in a world of warring kingdoms and dangerous magic.